REALIZATION OF INDIVIDUAL AND PERSONAL DEVELOPMENT POTENTIAL OF STUDENTS OF A SPECIAL MEDICAL GROUP IN THE PROCESS OF ADAPTIVE PHYSICAL EDUCATION - Zyryanov K.V.; Novikov I.I.; Murinchik E.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study. Adaptive physical education exerts a positive influence on students with flat-valgus foot deformity and other special needs. Regular training sessions contribute to significant improvements in physical parameters. Furthermore, positive changes in psychological state are observed: heightened self-esteem, increased self-confidence, and enhanced motivation. The training also promotes the development of social skills, improving interactions with others and reducing stress levels. An individual’s personal potential encompasses the totality of personal qualities, abilities, interests, and motivations that facilitate their development and successful self-realization in various spheres of life. For individuals with special health needs, realizing this potential can be challenging due to their specific circumstances; however, adaptive physical activity can assist in both realizing and accepting oneself. Methods and structure of the study. is to examine how adaptive physical education influences the realization of individual personal potential of students of a special medical group with flat-valgus foot deformity. The study involved 15 students aged 18 to 25 years, assigned to a special health needs group and diagnosed with flat-valgus foot deformity. The experiment revealed that adaptive physical education sessions have a positive impact on students with special needs, including those with flat-valgus foot deformity, encompassing various aspects of their lives. Physical improvements include increased strength, flexibility, and endurance, along with reduced pain sensations. Psychological outcomes demonstrate heightened self-esteem, increased self-confidence and motivation, and decreased stress levels. Emotional state also improves, evidenced by elevated mood and reduced anxiety. Social skills are strengthened through enhanced interaction with other students and increased comfort in the social environment.